Reasons Why Lawyers Recommend or Do Not Recommend Mediation to Their Clients - Kraemer , Raimonda (Teisė, 2021)
This article presents the results of a study of findings gathered by a survey of authors from Lithuania, Great Britain, Austria, and Germany. The author seeks to reveal the reasons why attorneys recommend or do not recommend mediation to their clients.